The conditional influence of poverty, inequality and severity of poverty on economic growth in Sub-Saharan Africa - Simplice Asongu; Joel Hinaunye Eita (African Governance and Development Institute (AGDI), 2023)
Poverty and inequality represent major policy syndromes that are relevant in the achievement of most United Nations' sustainable development goals (SDGs) in sub-Saharan Africa, while economic growth is also essential for the achievement of attendant SDGs. The present study extends existing literature by assessing the conditional influence of poverty, income inequality and severity of poverty on economic growth. The focus is on 42 countries in sub-Saharan Africa with data from 1980 to 2019. The Gini index is used to measure income inequality. Poverty is measured in terms of the poverty headcount ratio while the severity of poverty is computed as the squared of the poverty gap index. The empirical evidence is based on quantile regressions in order to assess how income inequality and poverty dynamics affect economic growth throughout the conditional distribution of economic growth. Our main finding shows that the negative response of economic growth to poverty is a decreasing function of economic growth. In other words, the incidence of poverty in reducing economic growth decreases with increasing levels of economic growth. In two specifications, the effect of inequality is negative in bottom quantiles and positive in top quantiles of the conditional distribution of economic growth. Policy implications are discussed, especially as it pertains to: (i) the relevance of poverty in mitigating economic growth in SSA contingent on initial levels of economic growth and (ii) comparative incidences of poverty and inequality in affecting economic growth.
Keywords: D31; I10; I32; K40; O55; 330; poverty; inequality; economic growth; sub-Saharan Africa; econometrics; economics